MHC class I diversity in chimpanzees and bonobos - Maibach, Vincent (Immunogenetics, 2017)
Major histocompatibility complex (MHC) class I genes are critically involved in the defense against intracellular pathogens. MHC diversity comparisons among samples of closely related taxa may reveal traces of past or ongoing selective processes. The bonobo and chimpanzee are the closest living evolutionary relatives of humans and last shared a common ancestor some 1 mya. However, little is known concerning MHC class I diversity in bonobos or in central chimpanzees, the most numerous and genetically diverse chimpanzee subspecies. Here, we used a long-read sequencing technology (PacBio) to sequence the classical MHC class I genes A, B, C, and A-like in 20 and 30 wild-born bonobos and chimpanzees, respectively, with a main focus on central chimpanzees to assess and compare diversity in those two species. We describe in total 21 and 42 novel coding region sequences for the two species, respectively. In addition, we found evidence for a reduced MHC class I diversity in bonobos as compared to central chimpanzees as well as to western chimpanzees and humans. The reduced bonobo MHC class I diversity may be the result of a selective process in their evolutionary past since their split from chimpanzees. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00251-017-0990-x) contains supplementary material, which is available to authorized users.